Discovery of Neopanorpa chillcotti Byers (Mecoptera: Panorpidae) from Tibet, China, with discussion of its generic status - Wang, Meng; Hua, Bao-Zhen (Zootaxa, 2017)
Neopanorpa chillcotti Byers, 1971 was originally described from Kathmandu in Nepal and is now found to be distributed in Gyirong, Tibet in China. The species is redescribed and illustrated based on new material from China and Nepal. The generic status of this species is briefly discussed.